3D-CO2-modelling for waste management in Styria/Austria - Fischer, Wolfgang; Simic, Danko (Journal for Geography, 2016)
The paper in hand focuses on a calculation model which had been developed for calculating the CO2 production of a garbage truck during a waste collection tour. The challenge is the integration of not only the distance and loading weight but also the different petrol consumption and therefore CO2 production in regard to the topography of the whole collection tour. Additionally the increase of waste load at each stop during the whole collection tour has to be taken into account for the calculation. The model has been developed on basis of Excel. In order to get the real data from the collection tours these had been accompanied. There not only the whole tour but also all waste bins and stops for loading the waste had been registered. Both GPS (Global Positioning System) and RFID (Radio-Frequency Identification) had been used. The huge amount of data had to be scrubbed. This process of amending or removing data in a database that is incorrect, incomplete, improperly formatted, or duplicated was an important step to have reliable data for further calculation processes. The identification of the CO2 production during a waste collection tour including the topography and continuous revenue load had not been done so far and allows the identification of tour segments with lower but mainly higher or very high ecological impact. However, this is the basis for further discussions about options for optimizing the actual tours and habits of waste collection. That approach is part of a more comprehensive investigation of waste collection tours with general focus on economic, ecologic and social potentials for optimization.
Keywords: waste management; CO2; production of trucks; Styria; Austria